PEMETAAN DATA DAN INFORMASI PENYUSUNAN PERENCANAAN PEMBANGUN DESA DI KECAMATAN TAMBANG KABUPATEN KAMPAR - aguswan, aguswan; Zuhdi, Sulaiman (Jurnal Niara, 2018)
Mapping of data and information on the preparation of village development planning dikecamatan Tambang Kabupaten Kampar. The preparation of village development planning is very important to be carried out by the village head and its equipment. The objectives of the village planning arranged for the village development plan can be discussed in the village development consultation forum. In this Forum the village development plan is matured, so it becomes the Village Development Plan. The preparation of village development planning can not be carried out properly, without complete data and information either in the implementation of village government, organization and governance of village administration, village finance, village profile and other information related to governance and community empowerment. The three villages that were used as research mapping object in Kampar sub-district Tambang were Tarai build village, Rimbo Panjang village and Tambang village. Village development planning in the three sample villages appears to be underdeveloped by complete data and information, and this has a major impact on the Village Mid Term Development Plan (RPJMDesa) and the Government-Village Action Plan (RKP -Desa) which guides development implementation in the countryside